2020
DOI: 10.1186/s13287-020-01974-3
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+-activated mitochondrial biogenesis and functions improve stem cell fate in Rg3-treated human mesenchymal stem cells

Abstract: Although mitochondrial functions are essential for cell survival, their critical roles in stem cell fate, including proliferation, differentiation, and senescence, remain elusive. Ginsenoside Rg3 exhibits various biological activities and reportedly increases mitochondrial biogenesis and respiration. Herein, we observed that Rg3 increased proliferation and suppressed senescence of human bone marrow-derived mesenchymal stem cells. Osteogenic, but not adipogenic, differentiation was facilitated by Rg3 treatment.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…TβRI and TβRII combine with TGF-β1 to form a TβRII-TGF-β1-TβRI heterotetramer complex. Smad2 and Smad3 can be activated by the complex and form a complex with Smad4, transferring the signal into the nucleus and so regulating the downstream gene expression. , Some studies have shown that Rg3 exhibits different biological activities and improves the human mesenchymal stem cell proliferation and differentiation . In addition, Rg3 promotes human endothelial cell proliferation via PI3K/Akt and MAPK/ERK pathways .…”
Section: Discussionmentioning
confidence: 99%
“…TβRI and TβRII combine with TGF-β1 to form a TβRII-TGF-β1-TβRI heterotetramer complex. Smad2 and Smad3 can be activated by the complex and form a complex with Smad4, transferring the signal into the nucleus and so regulating the downstream gene expression. , Some studies have shown that Rg3 exhibits different biological activities and improves the human mesenchymal stem cell proliferation and differentiation . In addition, Rg3 promotes human endothelial cell proliferation via PI3K/Akt and MAPK/ERK pathways .…”
Section: Discussionmentioning
confidence: 99%
“…After culturing, the cells were changed to pre-warmed XF DMEM medium (for OCR measurement, containing 1 M glucose, 100 mM pyruvate and 200 mM L-glutamate and adjusted at pH 7.4; Agilent Technologies) 1 h prior to analyses and kept cells at 37 °C without CO 2 . OCR was measured in human bone marrow stem cells (hBMSCs) using the Seahorse XFe96 Analyzer (Agilent Technologies) to determine the oxygen consumption in response to the addition of various chemicals [ 40 ]. The cycles (3 times for 3 min) were run for every measurement and the Mitostress kit (Agilent Technologies), containing the following compounds: 2 μM oligomycin (ATP synthase inhibitor), 2 μM carbonyl cyanide-4-(trifluoromethoxy) phenylhydrazone (FCCP) (mitochondrial uncoupler), 0.5 μM rotenone (respiratory chain complex I inhibitor), and antimycin A (complex III inhibitor), was used.…”
Section: Methodsmentioning
confidence: 99%
“…Ginsenoside Rg2 activates AMPK-mediated autophagy restores pig MSCs proliferation and inhibits oxidative stress-induced replicative senescence in pig MSCs ( Che et al, 2023 ). Ginsenoside Rg3 mainly enhances the biogenesis ability of mitochondria and antioxidant function by promoting Ca 2+ concentration properly, thus improving proliferation and differentiation potential and preventing human MSCs from aging ( Hong et al, 2020 ). These results suggest that administration of ginsenosides may be a promising approach to counteract MSC aging by intervening in oxidative stress-related pathways ( Figure 1 ).…”
Section: Effects Of Ginseng On Different Types Of Stem Cellsmentioning
confidence: 99%